On the true identity of Geophilus tropicus Brölemann, 1898, a geophilid species from Venezuela (Chilopoda Geophilomorpha Geophilidae) - Pereira, Luis Alberto (1997)
Fil: Pereira, Luis Alberto. División Zoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina